Determinants of climate change adaptation strategies in South India: Empirical evidence - Kumar, K. N. Ravi; Reddy, M. J. Mohan; Reddy, K. Viswanatha; Paramesha, Venkatesh; Balasubramanian, M.; Kumar, T. Kiran; Kumar, R. Mohan; Reddy, D. Damodar (Frontiers in Sustainable Food Systems, 2023)
The phenomena of climate change pose multifaceted challenges to crop and livestock farming, with severe implications on smallholder farmers’ income and livelihoods. Climate change has pro-found implications (economic, environmental, and social) predominantly on rainfed regions in developing countries like India agriculture constitutes the backbone of the economy. In this con-text, the current study analyzes how farmers perceive climate change in rainfed ecosystem in In-dia, farmers’ adaptation strategies, and their major determinants in addressing climate change. Data were collected from 400 sample farmers in southern India. Discriminant and Multinomial Logit Models were employed to identify the adaptation strategies of the farmers. It was evident that the factors such as off-farm income, farm income, and farming experience significantly in-fluenced the adaptation strategies for tackling climate change. Further, access to climate-change information and literacy level are vital determinants in different climate-change adaptation strat-egies viz., crop diversification, integrated farming system, contingency plans for farm operations, and adoption of soil and water conservation techniques. However, the study highlights the in-creasing role of institutions (government and private) in the future to safeguard the interests of farmers through offering a wide range of policy, research and technology interventions. In nut-shell, R&D focus on climate-resilient agriculture, application of ICTs in agro-advisory services, and creation off-farm employment opportunities for the farmers is crucial to sustaining their livelihoods, as they serve as potential mitigation strategies to impart resilience to climate-sensitive sectors like agriculture in rained ecosystems in India or any other countries.